Proxy representation of Arctic ocean bottom pressure variability: Bridging gaps in GRACE observations - Cecilia Peralta‐Ferriz; James H. Morison; John M. Wallace (Geophysical Research Letters)
Abstract Using time‐varying ocean bottom pressure (OBP) from the Gravity Recovery and Climate Experiment (GRACE), a 9 year in situ OBP record at the North Pole, and wind reanalysis products, we perform a linear regression analysis to identify primary predictor time series that enable us to create a proxy representation of the Arctic time‐varying OBP that explains the largest fraction of the observed Arctic OBP variability. After cross validation, two predictors—North Pole OBP record and wind‐OBP coupling from maximum covariance analysis—explain 50% of the total variance of the Arctic OBP. This work provides a means for bridging existing short gaps in GRACE measurements and potentially longer future gaps that may result if GRACE and its follow‐on mission do not overlap. The technique may be applicable to bridge gaps in GRACE measurements in other oceanic regions.